2016
DOI: 10.1515/jvetres-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

Bentonite diminishes DON-induced changes in bone development in mink dams

Abstract: Introduction: The aim of this study was to determine the effect of deoxynivalenol (DON), given alone or with bentonite (which eliminates mycotoxicity) in the diet of mink dams throughout mating, pregnancy, and lactation period to pelt harvesting, on the mechanical properties and geometry of their long bones. Material and Methods: The minks were randomly assigned into two groups: a control group (not supplemented with DON, n = 15) and a group fed naturally DON-contaminated wheat and divided into three sub-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
9
1
1
Order By: Relevance
“…Similar observation was made by Gibson et al ( 10 ), who found no weight loss in minks fed DON-contaminated feed at concentrations up to 0.62 mg·kg -1 . Opposite effect was noted in our earlier study with mink dams fed a diet containing DON-contaminated grains at the concentration of 3.7 mg·kg -1 , which resulted not only in growth inhibition and weight loss, but also led to reduction of bone length ( 24 ). It is suggested that minks are close in sensitivity to DON to swine, for which guidance level for mycotoxins in feed was set at 0.9 mg·kg -1 ( 10 , 17 ).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Similar observation was made by Gibson et al ( 10 ), who found no weight loss in minks fed DON-contaminated feed at concentrations up to 0.62 mg·kg -1 . Opposite effect was noted in our earlier study with mink dams fed a diet containing DON-contaminated grains at the concentration of 3.7 mg·kg -1 , which resulted not only in growth inhibition and weight loss, but also led to reduction of bone length ( 24 ). It is suggested that minks are close in sensitivity to DON to swine, for which guidance level for mycotoxins in feed was set at 0.9 mg·kg -1 ( 10 , 17 ).…”
Section: Discussionmentioning
confidence: 61%
“…The mechanical endurance depends on the body and bone mass, geometry, microarchitecture, and bone quality as a relationship of the mineralisation and bone matrix. Our study with mink dams exposed to DON at the concentration of 3.7 mg·kg -1 showed that mycotoxins reduced geometric and mechanical endurance as well as bone mineral density ( 24 ). However, neither BMD, as an important indicator of bone strength, nor BTD differed between DON-treated and non-exposed dams in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…another ingredient that may contribute to a higher growth rate is bentonite. It is known that it exhibits a tonic effect on the gastric mucosa and eliminates mycotoxicity (TOMASZEWSKA et al 2016). Many studies addressing poultry feeding requirements have shown that probiotics can prevent diseases associated with administration of pathogenic organisms, reduce the number of pathogenic organisms recovered from test birds, and reduce shedding of pathogenic organisms (SMITH 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen present in skin tissue is mainly collagen type I: 75%, type III: 22%, and type V: 3%, so the collagen type I to type III ratio is about 2.5 [33,34]. In our previous works, in which we examined the effect of DON and bentonite on bone mechanical properties in minks, we suggested that malnutrition resulting from the presence of mycotoxicosis in the diet could impaired synthesis of collagen type I [35,36]. Moreover, the effect of mycotoxins (DON, Ochratoxin A) on collagen synthesis was previously observed in studies performed cell lines, showing that mycotoxins can influence the expression of fibrous collagens, including collagen type III [37,38].…”
Section: Discussionmentioning
confidence: 99%